The Role of Woman's Autobiography in Creating and Recreating Stereotype Scenarios for Women, 23 April, 1987, Ferguson Center, University of Alabama, USA - Gjurgjan, Ljiljana Ina (1987)
Drawing on some contemporary women’s writing in particular by the Croatian authors S. Drakulić and I. Vrkljan, the lecture has theoretically investigated one of the prominent subversive strategies of women’s writing – the creation of the alternative role models in (auto)biographical and pseudo-biographical texts. Starting from the contention that the metaphors reflect as well as influence reality, it has been argued that the subversion of the traditional representation of women can have the liberating effect as it proves that there is a possibility to think and live differently.